Quadriceps myositis: an appraisal of the diagnostic criteria of quadriceps myopathy. - Mohr, P. D. (BMJ Group, 1977)
A patient with the clinical picture of quadriceps myopathy was shown to have an underlying myositis. Review of the literature showed myositis to be a rare cause of the 'quadriceps syndrome' but it is important to identify this group because they are potentially treatable with corticosteroids.